2015
DOI: 10.1007/s10549-015-3573-2
|View full text |Cite
|
Sign up to set email alerts
|

Pneumocystis jiroveci pneumonia (PCP) in patients receiving neoadjuvant and adjuvant anthracycline-based chemotherapy for breast cancer: incidence and risk factors

Abstract: Opportunistic infection with Pneumocystis jiroveci pneumonia (PCP) has not been recognized as a significant complication of early-stage breast cancer treatment. However, we have observed an increase in PCP incidence among patients receiving chemotherapy for early-stage breast cancer. Herein we identify risk factors for and calculate incidence of PCP in this population. We identified all cases of PCP at Dana-Farber Cancer Institute/Brigham and Women's Hospital (DFCI/BWH) from 1/1/2000 to 12/31/2013 in patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
28
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 31 publications
2
28
1
Order By: Relevance
“…Hematological cancer and chemotherapy were other leading immunocompromised factors. These findings are consistent with those in previous studies; patients recruited in observational studies include patients with solid or hematological cancer and those who underwent chemotherapy with associated neutropenia [15][16][17][18][19][20]22]. Dedicated guidelines and recommendations are available, especially on respiratory viruses, fungi, and P. jirovecii [23][24][25][26].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Hematological cancer and chemotherapy were other leading immunocompromised factors. These findings are consistent with those in previous studies; patients recruited in observational studies include patients with solid or hematological cancer and those who underwent chemotherapy with associated neutropenia [15][16][17][18][19][20]22]. Dedicated guidelines and recommendations are available, especially on respiratory viruses, fungi, and P. jirovecii [23][24][25][26].…”
Section: Discussionsupporting
confidence: 89%
“…Randomized controlled trials (RCTs) and observational prospective studies are missing owing to the fact that, generally, studies assessing management strategies for pneumonia exclude immunocompromised patients or take into account only a single specific risk factor [12][13][14][15][16][17][18][19][20][21]. This lack of information about immunocompromise could lead to both underestimation of the real prevalence with a higher rate of treatment failure and to overestimation and overuse of wide-spectrum antibiotics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whilst it has been described in HIV-negative patients with advanced solid tumours, it is not a well-recognized complication of EBC treatment, with data largely confined to single case reports or small case series only. More recently, Waks et al identified 19 cases of PJP amongst a series of 2057 patients receiving the ddAC-containing regimen for EBC [9]. All 19 cases were diagnosed after at least three doses of AC chemotherapy on a dose-dense schedule, giving an overall incidence of 0.6% (95% confidence interval 0.3-1.0%).…”
Section: Discussionmentioning
confidence: 99%
“…However, the use of corticosteroids in chemotherapy regimens has been consistently reported as a major risk factor (8). Recently, there have been isolated reports of PCP in patients on dose-dense AC chemotherapy for early breast cancer (9)(10)(11). In the dose-dense AC regimen, these agents are administered on an every-twoweeks schedule, while in the standard AC regimen, they are administered on an every-three-weeks schedule.…”
Section: Discussionmentioning
confidence: 99%